Protein Kinase Cα-Induced Derepression of the Human Luteinizing Hormone Receptor Gene Transcription through ERK-Mediated Release of HDAC1/Sin3A Repressor Complex from Sp1 Sites - Liao, Mingjuan; Zhang, Ying; Dufau, Maria L. (Molecular endocrinology (Baltimore, Md.), 2008)
Abstract LH receptor (LHR) gene transcription is subject to repression/derepression through various modes and multiple effectors. Epigenetic silencing and activation of the LHR is achieved through coordinated regulation at both histone and DNA levels. The LHR gene is subject to repression by deacetylation and methylation at its promoter region, where a HDAC/mSin3A repressor complex is anchored at Sp1 sites. The present studies revealed that protein kinase C (PKC) α/ERK signaling is important for the activation of LHR promoter activity, and the increase of endogenous transcripts induced by phorbol-12-myristate-13-acetate (PMA) in HeLa cells. Whereas these effects were attributable to PKCα activity, the ERK pathway was the downstream effector in LHR activation. PMA caused a significant enhancement of Sp1 phosphorylation at serine residue (s), which was blocked by PKCα or ERK inhibition. The interaction of activated phosphorylated ERK with Sp1 and ERK’s association with the LHR promoter points to Sp1 as a direct target of ERK. After Sp1 phosphorylation, the HDAC1/mSin3A repressor complex dissociated from Sp1 sites, histone 3 was acetylated, and transcription factor II B and RNA polymerase II were recruited. In addition, overexpression of a constitutively active PKCα (PKCα CA) strongly activated LHR transcription in MCF-7 cells (devoid of PKCα), induced Sp1 phosphorylation at serine residue (s) and caused derecruitment of HDAC1/mSin3A complex from the promoter. These effects were negated by cotransfection of a dominant-negative PKCα. In conclusion, these studies have revealed a novel regulatory signaling mechanism of transcriptional control in which the LHR is derepressed through PKCα/ERK-mediated Sp1 phosphorylation, causing the release of HDAC1/mSin3A complex from the promoter.